Magnetic material for hyperthermia treatment and manufacturing method thereof
Patent Information
- Application Number
- JP2023137764
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-28
- Publication Date
- 2025-03-12
AI Technical Summary
【0012】 本発明の窒化鉄微粒子は優れた発熱特性を示すので、温熱治療効果を更に高めることができる。また、患者への投与量を減らすこともでき、患者にさらに優しい治療の実現だけでなく、医療費の低減にもつながる。本発明のより具体的な態様によれば、温熱治療用磁性体として先行品であるマグネタイトナノ粒子(Fe3O4ナノ粒子)を上回る発熱効率により、温熱治療効果を高め、がん細胞をより効率よく焼灼できる磁性粒子としての開発が期待される。また、発熱効率の向上により磁性粒子の投与量の削減、及び交流磁場発生装置の規模縮小も期待される。
Smart Images

Figure 2025032481000003 
Figure 2025032481000004 
Figure 2025032481000005
Abstract
Description
[Technical field]
[0001] The present invention relates to a magnetic material for hyperthermia treatment and a manufacturing method thereof, and more specifically, to a magnetic material for hyperthermia treatment containing iron nitride and a manufacturing method thereof. [Background technology]
[0002] Cancer cells are sensitive to heat and die at temperatures above 43°C, but normal cells can survive up to about 48°C. Magnetic materials such as magnetite generate heat when placed under an alternating magnetic field. Therefore, by sending a magnetic material to the affected area and placing the affected area under an alternating magnetic field, it is possible to kill cancer cells by heat (hyperthermia). In Europe, a magnetic fluid with magnetite nanoparticles dispersed therein (Non-Patent Document 4) has been developed as a magnetic material for hyperthermia therapy and is used to treat malignant brain tumors.
[0003] Magnetite has been the main researched magnetic material for hyperthermia. Research and development has been carried out for several decades, and it has finally been put to practical use in Europe, as mentioned above. On the other hand, if the heat generation efficiency of magnetic materials could be further improved, there would be great clinical benefits, such as further enhancing the effects of hyperthermia and reducing the amount of drug administered to patients. In other words, there is magnetic hyperthermia, a type of hyperthermia treatment that uses magnetite (Fe3O4) as a heating species. However, the heating properties of Fe3O4 are not high enough to provide sufficient therapeutic effects against cancer. Therefore, it is important to search for heating species that have superior heating properties to Fe3O4. To date, Fe x N y Attempts have been made to use nanoparticles in hyperthermia, and their usefulness has been suggested (Non-Patent Documents 1-2). x N y The synthesis of nanoparticles has the problem that it requires toxic ammonia gas as a nitrogen source.
[0004] In Europe, a magnetic fluid (trade name: NanoTherm (registered trademark) liquid) in which magnetite nanoparticles whose surfaces are modified with aminosilane are dispersed in oil has been developed and is being used to treat malignant brain tumors. Clinical research is also underway for pancreatic cancer, prostate cancer, breast cancer, and esophageal cancer. The inventors have also developed a magnetic fluid that mainly consists of Fe 16 Although iron nitride fine particles made of N2 have been reported (Non-Patent Documents 1-2), their heat generating properties are unclear.
[0005] To improve the effect of hyperthermia treatment, it is necessary to further improve the heat generation properties of magnetic materials. However, magnetite has been researched and developed for the past several decades, so its heat generation properties are likely to have already reached their limit. Magnetic microspheres with a diameter of about 25 microns can be introduced into capillaries near the affected area, blocking the capillaries to supply nutrients to the cancer, and at the same time, it is possible to heat the cancer from there and treat it (intravascular hyperthermia therapy). However, such magnetic microspheres have not been proposed other than magnetite microspheres reported by the present inventors in 2005 (Non-Patent Document 5). Other patent documents related to iron nitride include Patent Documents 1 and 2, and patent documents related to Fe3O4 microspheres include Patent Documents 3 and 4. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2013-80922 A [Patent Document 2] JP 2013-69926 A [Patent Document 3] JP 2004-105722 A [Patent Document 4] Patent Application No. 2005-505691 [Non-patent literature]
[0007] [Non-Patent Document 1] M. Shibata et al., Ceram. Int., 45 (2019) 23707-23714. [Non-Patent Document 2] M. Shibata et al., J. Biomed. Mater. Res., 109 (2021) 1784-1791. [Non-Patent Document 3] A. Miura et al., Inorg. Chem., 52 (2013) 11787-11791. [Non-Patent Document 4] B. Thiesen et al., Hyperthermia, 24 (2008) 467-74. [Non-Patent Document 5] M. Kawashita et al., Biomaterials, 26 (2005) 2231-8. Summary of the Invention [Problem to be solved by the invention]
[0008] Therefore, an object of the present invention is to provide a magnetic material for hyperthermia that exhibits excellent heat generation properties. [Means for solving the problem]
[0009] Since the heat generation characteristics of magnetic materials are related to their magnetic properties, the present inventors focused on iron nitride fine particles that exhibit magnetic properties superior to those of magnetite, and focused on iron nitride that exhibits ferromagnetism and high saturation magnetization. The present inventors have developed a simple ε-Fe 2-3 The material was synthesized based on the synthesis method of N (see Non-Patent Document 3 above), and the effect of differences in synthesis conditions on the heat generation properties was investigated. 2-3 The application potential of N nanoparticles as a thermogenic species was explored.
[0010] As a result of extensive research, the inventors have found that Fe-based magnetite, which exhibits superior heat generation properties compared to magnetite, is a material that is mainly composed of Fe. 2-3The researchers obtained iron nitride particles consisting of N. Specifically, when hematite and sodium amide were enclosed in a high-pressure reaction and decomposition vessel and heated in an incubator at 250°C for 12 hours, iron nitride particles exhibiting excellent heat generation properties were obtained.
[0011] That is, the present invention provides the following. [Aspect 1] A magnetic material for hyperthermia treatment comprising iron nitride, wherein the number of nitrogen atoms in said iron nitride measured by EDS mapping is 35% to 5% of the total number of atoms in said iron nitride. [Aspect 2] 2. The magnetic material for hyperthermia treatment according to aspect 1, wherein the number of nitrogen atoms in the iron nitride is 27% to 7% with respect to the total number of atoms in the iron nitride. [Aspect 3] 2. The magnetic material for hyperthermia treatment according to aspect 1, wherein the number of nitrogen atoms in the iron nitride is 25% to 9% with respect to the total number of atoms in the iron nitride. [Aspect 4] 2. The magnetic material for hyperthermia treatment according to aspect 1, wherein the number of nitrogen atoms in the iron nitride is 24% to 10% with respect to the total number of atoms in the iron nitride. [Aspect 5] 2. A magnetic material for hyperthermia treatment according to aspect 1, wherein the number of iron atoms in the iron nitride is 20% to 80% of the total number of atoms in the iron nitride. [Aspect 6] 2. A magnetic material for hyperthermia treatment according to aspect 1, wherein the number of iron atoms in the iron nitride is 30% to 75% of the total number of atoms in the iron nitride. [Aspect 7] 2. The magnetic material for hyperthermia treatment according to aspect 1, wherein the number of iron atoms in the iron nitride is 40% to 70% of the total number of atoms in the iron nitride. [Aspect 8] 2. A magnetic material for hyperthermia treatment according to aspect 1, wherein the number of iron atoms in the iron nitride is 50% to 65% of the total number of atoms in the iron nitride. [Aspect 9] 1. A magnetic material for hyperthermia treatment comprising iron nitride, wherein a 2θ peak is measured at 42° to 44° in an X-ray diffraction measurement of said iron nitride. [Aspect 10] 10. The magnetic substance for hyperthermia treatment according to aspect 9, wherein a 2θ peak is measured at 42.5° to 44.0° by X-ray diffraction measurement of the iron nitride. [Aspect 11] 10. The magnetic substance for hyperthermia treatment according to aspect 9, wherein a 2θ peak is measured at 43.0° to 43.7° by X-ray diffraction measurement of the iron nitride. [Aspect 12] 10. The magnetic substance for hyperthermia treatment according to aspect 9, wherein a 2θ peak is measured at 43.2° to 43.7° by X-ray diffraction measurement of the iron nitride. [Aspect 13] A method for producing a magnetic material for hyperthermia containing iron nitride, comprising heating a raw material for iron nitride at 230 to 270°C for 3 to 120 hours. [Aspect 14] 14. The method of claim 13, comprising heating the iron nitride source for 6 hours to 50 hours. [Aspect 15] 14. The method of claim 13, comprising heating the iron nitride source for 9 hours to 20 hours. [Aspect 16] 14. The method of claim 13, comprising heating the iron nitride source at 235-265 °C. [Aspect 17] 14. The method of claim 13, comprising heating the iron nitride source at 245-255 °C. [Aspect 18] 14. The method of claim 13, wherein the source of iron nitride comprises hematite and sodium amide. [Aspect 19] A method for hyperthermia treatment, comprising using the magnetic material for hyperthermia treatment according to any one of aspects 1 to 12. [Aspect 20] 20. The thermotherapy method according to aspect 19, which is a method for treating cancer. Effect of the Invention
[0012] The iron nitride microparticles of the present invention exhibit excellent heat generating properties, and therefore can further enhance the effects of hyperthermia treatment. In addition, the amount of drug administered to the patient can be reduced, which not only realizes more patient-friendly treatment but also leads to a reduction in medical costs. According to a more specific embodiment of the present invention, the heat generating efficiency exceeds that of magnetite nanoparticles (Fe3O4 nanoparticles), which are the predecessor magnetic substances for hyperthermia treatment, and it is expected that the magnetic particles can be developed to enhance the effects of hyperthermia treatment and cauterize cancer cells more efficiently. Furthermore, the improved heat generating efficiency is expected to reduce the amount of magnetic particles administered and the scale of AC magnetic field generators. [Brief description of the drawings]
[0013] [Figure 1] Figure 1 is a graph showing the heat generation characteristics of samples synthesized at 230 to 260 °C for 12 hours (Tukey's test, **P < 0.01, ***P < 0.001; n = 4). [Diagram 2] In FIG. 2, the left figure shows the XRD peaks (2θ = 20 to 80°) when the reaction time was changed from 6 to 96 hours, and the right figure shows the transition of the peak shift (2θ = 38 to 48°) (see H. Jacobs, et al., Alloys Compds. 227 (1995) 10; Pinsker, G., Dokl.Akad. Nauk, SSSR96 (1954) 519). All peaks shifted from Fe2N to Fe3N, and it became clear that the increase in reaction time caused a decrease in the amount of nitrogen. [Diagram 3] In Figure 3, the left figure shows the XRD peaks (2θ = 20 to 80°) when the reaction temperature was changed from 230 to 260°C, and the right figure shows the change in peak intensity (2θ = 41 to 45°). From the change in peak intensity depending on the reaction temperature, the transition of the integral breadth was understood, and the crystallite size was derived from the Scherrer formula, confirming the increase in crystallite size. [Figure 4] Figure 4 is a photograph showing the results of EDS mapping. The numbers in the lower right corner of the figure indicate the atomic percentages of iron, oxygen, and nitrogen in the entire mapping image. [Diagram 5] Figure 5 is a graph showing the heat generation characteristics of the sample synthesized at 240 °C for 96 hours (Tukey's test; **P < 0.01, n = 4). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] The present invention provides a magnetic material for hyperthermia therapy comprising iron nitride, wherein the number of nitrogen atoms in the iron nitride measured by EDS mapping is 35% to 5% relative to the total number of atoms in the iron nitride.
[0015] EDS mapping is one of the methods of elemental analysis using characteristic X-rays. It is a method to visualize the distribution of elements in a sample by displaying the intensity distribution of characteristic X-rays or the concentration distribution of elements of a specified element in a specified area in two dimensions. In elemental mapping by energy dispersive X-ray spectroscopy (EDS), an electron beam is used to scan the area to be analyzed in two dimensions, and the characteristic X-ray spectrum generated is obtained for each pixel. From these spectra, the X-ray intensity or element concentration of the analyzed element is calculated and displayed at each pixel to obtain an elemental map. There are three types of elemental maps in EDS, two of which are characteristic X-ray intensity maps and one is an elemental concentration map. An elemental concentration map (quantitative map) is a map in which the elemental concentration is calculated and displayed for each pixel in the mapping area, and is generally referred to as a "quantitative map." An elemental concentration map (quantitative map) is obtained in the following way. First, the X-ray intensity of the spectrum at each pixel (p) is normalized to the intensity obtained under the same measurement conditions as the standard spectrum. Next, the coefficient (tp) is obtained in the same way as the net map. The coefficient obtained in the normalized state is the ratio of the X-ray intensity of the standard sample to that of the unknown sample, and is called the K ratio (Kp). In addition, the correction factor (Gp), which represents the difference in X-ray intensity due to the difference in the coexisting elements between the standard sample and the unknown sample, is obtained using the ZAF correction or the φ(ρz) method. If the concentration of the standard sample is Cstd, the element concentration at each pixel (p) is obtained from the following formula.
number
[0016] The magnetic material for thermotherapy containing iron nitride provided by the present invention has a number of nitrogen atoms in the iron nitride measured by EDS mapping that is, for example, 35% or less, 34% or less, 33% or less, 32% or less, 31% or less, 30% or less, 29% or less, 28% or less, 27% or less, 26% or less, 25% or less, 24% or less, 23% or less, 22% or less, 21% or less, 20% or less, 19% or less, 18% or less, 17% or less, 16% or less, 15% or less, 14% or less, 13% or less, 12% or less, 11% or less, or 10% or less of the total number of atoms in the iron nitride.
[0017] The magnetic material for thermotherapy containing iron nitride provided by the present invention has a number of nitrogen atoms in the iron nitride measured by EDS mapping relative to the total number of atoms in the iron nitride, which is, for example, 7% or more, 8% or more, 9% or more, 10% or more, 11% or more, 12% or more, 13% or more, 14% or more, 15% or more, 16% or more, 17% or more, 18% or more, 19% or more, 20% or more, 21% or more, 22% or more, 23% or more, 24% or more, 25% or more, 26% or more, 27% or more, 28% or more, 29% or more, or 30% or more.
[0018] In the magnetic material for hyperthermia containing iron nitride provided by the present invention, the number of nitrogen atoms in the iron nitride measured by EDS mapping is within a range specified by, for example, any of the above-mentioned upper limits and any of the above-mentioned lower limits with respect to the total number of atoms in the iron nitride.
[0019] The magnetic material for hyperthermia containing iron nitride provided by the present invention has a number of iron atoms in the iron nitride measured by EDS mapping that is, for example, 80% or less, 79% or less, 78% or less, 77% or less, 76% or less, 75% or less, 74% or less, 73% or less, 72% or less, 71% or less, 70% or less, 69% or less, 68% or less, 67% or less, 66% or less, 65% or less, 64% or less, 63% or less, 62% or less, 61% or less, 60% or less, 59% or less, or a range of .... or less, 58% or less, 57% or less, 56% or less, 55% or less, 54% or less, 53% or less, 52% or less, 51% or less, 50% or less, 49% or less, 48% or less, 47% or less, 46% or less, 45% or less, 44% or less, 43% or less, 42% or less, 41% or less, 40% or less, 39% or less, 38% or less, 37% or less, 36% or less, 35% or less, 34% or less, 33% or less, 32% or less, 31% or less, 30% or less, 29% or less, 28% or less, 27% or less, 26% or less, or 25% or less.
[0020] The magnetic material for hyperthermia containing iron nitride provided by the present invention has a number of iron atoms in the iron nitride measured by EDS mapping that is, for example, 20% or more, 21% or more, 22% or more, 23% or more, 24% or more, 25% or more, 26% or more, 27% or more, 28% or more, 29% or more, 30% or more, 31% or more, 32% or more, 33% or more, 34% or more, 35% or more, 36% or more, 37% or more, 38% or more, 39% or more, 40% or more, 41% or more, or more, 42% or more, 43% or more, 44% or more, 45% or more, 46% or more, 47% or more, 48% or more, 49% or more, 50% or more, 51% or more, 52% or more, 53% or more, 54% or more, 55% or more, 56% or more, 57% or more, 58% or more, 59% or more, 60% or more, 61% or more, 62% or more, 63% or more, 64% or more, 65% or more, 66% or more, 67% or more, 68% or more, 69% or more, 70% or more, 71% or more, 72% or more, 73% or more, 74% or more, or 75% or more.
[0021] In the magnetic material for hyperthermia containing iron nitride provided by the present invention, the number of iron atoms in the iron nitride measured by EDS mapping is within a range specified by, for example, any of the above-mentioned upper limits and any of the above-mentioned lower limits with respect to the number of all atoms in the iron nitride.
[0022] The magnetic material for hyperthermia containing iron nitride provided by the present invention has a ratio of the number of iron atoms in the iron nitride measured by EDS mapping to the number of nitrogen atoms in the iron nitride, which is, for example, 6.5 times or less, 6.4 times or less, 6.3 times or less, 6.2 times or less, 6.1 times or less, 6.0 times or less, 5.9 times or less, 5.8 times or less, 5.7 times or less, 5.6 times or less, 5.5 times or less, 5.4 times or less, 5.3 times or less, 5.2 times or less, 5.1 times or less, 5.0 times or less, 4.9 times or less, 4.8 times or less, or 5.8 times or less. times or less, 4.7 times or less, 4.6 times or less, 4.5 times or less, 4.4 times or less, 4.3 times or less, 4.2 times or less, 4.1 times or less, 4.0 times or less, 3.9 times or less, 3.8 times or less, 3.7 times or less, 3.6 times or less, 3.5 times or less, 3.4 times or less, 3.3 times or less, 3.2 times or less, 3.1 times or less, 3.0 times or less, 2.9 times or less, 2.8 times or less, 2.7 times or less, 2.6 times or less, 2.5 times or less, 2.4 times or less, 2.3 times or less, 2.2 times or less, 2.1 times or less, or 2.0 times or less.
[0023] The magnetic material for hyperthermia containing iron nitride provided by the present invention has a number of iron atoms in the iron nitride measured by EDS mapping that is, for example, 1.5 times or more, 1.6 times or more, 1.7 times or more, 1.8 times or more, 1.9 times or more, 2.0 times or more, 2.1 times or more, 2.2 times or more, 2.3 times or more, 2.4 times or more, 2.5 times or more, 2.6 times or more, 2.7 times or more, 2.8 times or more, 2.9 times or more, 3.0 times or more, 3.1 times or more, 3.2 times or more, or a ratio of the number of iron atoms in the iron nitride to the number of nitrogen atoms in the iron nitride. fold or more, 3.3 fold or more, 3.4 fold or more, 3.5 fold or more, 3.6 fold or more, 3.7 fold or more, 3.8 fold or more, 3.9 fold or more, 4.0 fold or more, 4.1 fold or more, 4.2 fold or more, 4.3 fold or more, 4.4 fold or more, 4.5 fold or more, 4.6 fold or more, 4.7 fold or more, 4.8 fold or more, 4.9 fold or more, 5.0 fold or more, 5.1 fold or more, 5.2 fold or more, 5.3 fold or more, 5.4 fold or more, 5.5 fold or more, 5.6 fold or more, 5.7 fold or more, 5.8 fold or more, 5.9 fold or more, or 6.0 fold or more.
[0024] In the magnetic material for hyperthermia containing iron nitride provided by the present invention, the number of iron atoms in the iron nitride measured by EDS mapping is within a range specified by, for example, any of the above-mentioned upper limits and any of the above-mentioned lower limits, relative to the number of nitrogen atoms in the iron nitride.
[0025] In the magnetic material for hyperthermia containing iron nitride provided by the present invention, the iron nitride may contain oxygen. In this case, the magnetic material for hyperthermia containing iron nitride provided by the present invention is such that the number of oxygen atoms in the iron nitride measured by EDS mapping is, for example, 60% or less, 59% or less, 58% or less, 57% or less, 56% or less, 55% or less, 54% or less, 53% or less, 52% or less, 51% or less, 50% or less, 49% or less, 48% or less, 47% or less, 46% or less, 45% or less, 44% or less, 43% or less, 42% or less, 41% or less, 40% or less, 39% or less, 38% or less, or 49% or less. %, 37% or less, 36% or less, 35% or less, 34% or less, 33% or less, 32% or less, 31% or less, 30% or less, 29% or less, 28% or less, 27% or less, 26% or less, 25% or less, 24% or less, 23% or less, 22% or less, 21% or less, 20% or less, 19% or less, 18% or less, 17% or less, 16% or less, 15% or less, 14% or less, 13% or less, 12% or less, 11% or less, 10% or less, 9% or less, 8% or less, 7% or less, 6% or less, 5% or less, 4% or less, 3% or less, 2% or less, or 1% or less.
[0026] In the magnetic material for hyperthermia containing iron nitride provided by the present invention, when the iron nitride contains oxygen, the magnetic material for hyperthermia containing iron nitride provided by the present invention has a number of oxygen atoms in the iron nitride measured by EDS mapping that is, for example, 1% or more, 2% or more, 3% or more, 4% or more, 5% or more, 6% or more, 7% or more, 8% or more, 9% or more, 10% or more, 11% or more, 12% or more, 13% or more, 14% or more, 15% or more, 16% or more. or more, 17% or more, 18% or more, 19% or more, 20% or more, 21% or more, 22% or more, 23% or more, 24% or more, 25% or more, 26% or more, 27% or more, 28% or more, 29% or more, 30% or more, 31% or more, 32% or more, 33% or more, 34% or more, 35% or more, 36% or more, 37% or more, 38% or more, 39% or more, 40% or more, 41% or more, 42% or more, 43% or more, 44% or more, 45% or more, 46% or more, 47% or more, 48% or more, 49% or more, or 50% or more.
[0027] In the magnetic material for hyperthermia therapy containing iron nitride provided by the present invention, when the iron nitride contains oxygen, the number of oxygen atoms in the iron nitride measured by EDS mapping in the magnetic material for hyperthermia therapy containing iron nitride provided by the present invention is within a range specified by, for example, any of the above-mentioned upper limits and any of the above-mentioned lower limits with respect to the number of all atoms in the iron nitride.
[0028] In the magnetic material for hyperthermia therapy containing iron nitride provided by the present invention, when the iron nitride contains oxygen, the number of oxygen atoms in the iron nitride measured by EDS mapping is 2.3 times or less, 2.2 times or less, 2.1 times or less, 2 times or less, 1.9 times or less, 1.8 times or less, 1.7 times or less, 1.6 times or less, 1.5 times or less, 1.4 times or less, 1.3 times or less, 1.2 times or less, 1.1 times or less, 1.0 times or less, 0.9 times or less, 0.8 times or less, or 0.7 times or less than the number of nitrogen atoms in the iron nitride.
[0029] In the magnetic material for hyperthermia therapy containing iron nitride provided by the present invention, when the iron nitride contains oxygen, the number of oxygen atoms in the iron nitride measured by EDS mapping is 0.6 times or more, 0.7 times or more, 0.8 times or more, 0.9 times or more, 1.0 times or more, 1.1 times or more, 1.2 times or more, 1.3 times or more, 1.4 times or more, 1.5 times or more, 1.6 times or more, 1.7 times or more, 1.8 times or more, 1.9 times or more, 2.0 times or more, 2.1 times or more, or 2.2 times or more relative to the number of nitrogen atoms in the iron nitride.
[0030] In the magnetic material for hyperthermia therapy containing iron nitride provided by the present invention, when the iron nitride contains oxygen, the number of oxygen atoms in the iron nitride measured by EDS mapping, relative to the number of nitrogen atoms in the iron nitride, is within a range specified by, for example, any of the above-mentioned upper limits and any of the above-mentioned lower limits.
[0031] The present invention provides a magnetic material for hyperthermia treatment containing iron nitride, in which a 2θ peak is measured at 42° to 44° by X-ray diffraction measurement of the iron nitride. More specifically, the X-ray diffraction measurement is performed using a desktop X-ray diffractometer (MiniFlex600) manufactured by Rigaku under the conditions described in the instructions. Specifically, the measurements and calculations are performed under the following conditions. X-ray source:CuKα Voltage: 40 kV, current: 15 mA, 2θ scan rate: 10° / min.
[0032] In the magnetic material for hyperthermia containing iron nitride provided by the present invention, a 2θ peak is measured at 42° to 44° by X-ray diffraction measurement of the iron nitride, but this does not mean that the 2θ peak is measured only at 42° to 44°, and other 2θ peaks may also be measured. However, in the magnetic material for hyperthermia containing iron nitride provided by the present invention, preferably, a 2θ peak is measured as the highest peak at 42° to 44° by X-ray diffraction measurement of the iron nitride.
[0033] The magnetic material for hyperthermia containing iron nitride provided by the present invention has, by X-ray diffraction measurement of the iron nitride, a 2θ peak at, for example, 42.0° or more, 42.1° or more, 42.2° or more, 42.3° or more, 42.4° or more, 42.5° or more, 42.6° or more, 42.7° or more, 42.8° or more, 42.9° or more, 43.0° or more, 43.1° or more, 43.2° or more, 43.3° or more, 43.4° or more, 43.5° or more, 43.6° or more, 43.7° or more, 43.8° or more, or 43.9° or more.
[0034] The magnetic material for hyperthermia containing iron nitride provided by the present invention has, by X-ray diffraction measurement of the iron nitride, a 2θ peak measured at, for example, 44.0° or less, 43.9° or less, 43.8° or less, 43.7° or less, 43.6° or less, 43.5° or less, 43.4° or less, 43.3° or less, 43.2° or less, 43.1° or less, 43.0° or less, 42.9° or less, 42.8° or less, 42.7° or less, 42.6° or less, 42.5° or less, 42.4° or less, 42.3° or less, 42.2° or less, or 42.1° or less.
[0035] The magnetic material for hyperthermia containing iron nitride provided by the present invention has, for example, a 2θ peak measured in a range specified by any of the above-mentioned upper limits and any of the above-mentioned lower limits by X-ray diffraction measurement of the iron nitride.
[0036] In the magnetic material for hyperthermia containing iron nitride provided by the present invention, the average particle size of the iron nitride is, for example, 500 nm or less, 450 nm or less, 400 nm or less, 350 nm or less, 300 nm or less, 250 nm or less, 200 nm or less, or 150 nm or less.
[0037] In the magnetic material for hyperthermia containing iron nitride provided by the present invention, the average particle size of the iron nitride is, for example, 100 nm or more, 150 nm or more, 200 nm or more, 250 nm or more, 300 nm or more, 350 nm or more, 400 nm or more, or 450 nm or more.
[0038] The magnetic material for hyperthermia containing iron nitride provided by the present invention has an average particle size of iron nitride within a range specified by, for example, any of the above-mentioned upper limits and any of the above-mentioned lower limits.
[0039] In the magnetic material for thermotherapy containing iron nitride provided by the present invention, the average crystallite size of the iron nitride is, for example, 17.5 nm or less, 17.0 nm or less, 16.5 nm or less, 16.0 nm or less, 15.5 nm or less, 15.0 nm or less, 14.5 nm or less, 14.0 nm or less, 13.5 nm or less, 13.0 nm or less, 12.5 nm or less, 12.0 nm or less, 11.5 nm or less, 11.0 nm or less, or 10.5 nm or less.
[0040] In the magnetic material for hyperthermia containing iron nitride provided by the present invention, the average crystallite size of the iron nitride is, for example, 10.0 nm or more, 10.5 nm or more, 11.0 nm or more, 11.5 nm or more, 12.0 nm or more, 12.5 nm or more, 13.0 nm or more, 13.5 nm or more, 14.0 nm or more, 14.5 nm or more, 15.0 nm or more, 15.5 nm or more, 16.0 nm or more, 16.5 nm or more, or 17.0 nm or more.
[0041] The magnetic material for hyperthermia containing iron nitride provided by the present invention has an average crystallite size of iron nitride within a range specified by, for example, any of the above upper limits and any of the above lower limits.
[0042] The present invention provides a method for producing a magnetic material for thermotherapy containing iron nitride, the method comprising heating a raw material for iron nitride at 230 to 270° C. for 3 to 120 hours.
[0043] In the method for producing a magnetic material for hyperthermia containing iron nitride provided by the present invention, the temperature at which the raw material for iron nitride is heated is, for example, 270°C or less, 269°C or less, 268°C or less, 267°C or less, 266°C or less, 265°C or less, 264°C or less, 263°C or less, 262°C or less, 261°C or less, 260°C or less, 259°C or less, 258°C or less, 257°C or less, 256°C or less, 255°C or less, 254°C or less. or less, 253°C or less, 252°C or less, 251°C or less, 250°C or less, 249°C or less, 248°C or less, 247°C or less, 246°C or less, 245°C or less, 244°C or less, 243°C or less, 242°C or less, 241°C or less, 240°C or less, 239°C or less, 238°C or less, 237°C or less, 236°C or less, 235°C or less, 234°C or less, 233°C or less, 232°C or less, or 231°C or less.
[0044] In the method for producing a magnetic material for hyperthermia containing iron nitride provided by the present invention, the temperature at which the raw material of iron nitride is heated is, for example, 230°C or higher, 231°C or higher, 232°C or higher, 233°C or higher, 234°C or higher, 235°C or higher, 236°C or higher, 237°C or higher, 238°C or higher, 239°C or higher, 240°C or higher, 241°C or higher, 242°C or higher, 243°C or higher, 244°C or higher, 245°C or higher, 246°C or higher, or higher, 247°C or higher, 248°C or higher, 249°C or higher, 250°C or higher, 251°C or higher, 252°C or higher, 253°C or higher, 254°C or higher, 255°C or higher, 256°C or higher, 257°C or higher, 258°C or higher, 259°C or higher, 260°C or higher, 261°C or higher, 262°C or higher, 263°C or higher, 264°C or higher, 265°C or higher, 266°C or higher, 267°C or higher, 268°C or higher, or 269°C or higher.
[0045] In the method for producing a magnetic material for hyperthermia containing iron nitride provided by the present invention, the temperature at which the raw material for iron nitride is heated is within a range specified by, for example, any of the above upper limits and any of the above lower limits.
[0046] In the method for producing a magnetic material for hyperthermia containing iron nitride provided by the present invention, the time for heating the raw material of iron nitride is, for example, 120 hours or less, 119 hours or less, 118 hours or less, 117 hours or less, 116 hours or less, 115 hours or less, 114 hours or less, 113 hours or less, 112 hours or less, 111 hours or less, 110 hours or less, 109 hours or less, 108 hours or less, 107 hours or less, 106 hours or less, 105 hours or less, 104 hours or less, 103 hours or less, 102 hours or less, 101 hours or less, 100 hours or less, 99 hours or less, or less than 98 hours, less than 97 hours, less than 96 hours, less than 95 hours, less than 94 hours, less than 93 hours, less than 92 hours, less than 91 hours, less than 90 hours, less than 89 hours, less than 88 hours, less than 87 hours, less than 86 hours, less than 85 hours, less than 84 hours, 8 3 hours or less, 82 hours or less, 81 hours or less, 80 hours or less, 79 hours or less, 78 hours or less, 77 hours or less, 76 hours or less, 75 hours or less, 74 hours or less, 73 hours or less, 72 hours or less, 71 hours or less, 70 hours or less, 69 hours or less, 68 hours or less, 6 7 hours or less, 66 hours or less, 65 hours or less, 64 hours or less, 63 hours or less, 62 hours or less, 61 hours or less, 60 hours or less, 59 hours or less, 58 hours or less, 57 hours or less, 56 hours or less, 55 hours or less, 54 hours or less, 53 hours or less, 52 hours or less, 51 hours or less, 50 hours or less, 49 hours or less, 48 hours or less, 47 hours or less, 46 hours or less, 45 hours or less, 44 hours or less, 43 hours or less, 42 hours or less, 41 hours or less, 40 hours or less, 39 hours or less, 38 hours or less, 37 hours or less, 36 hours or less, 35 hours or less, 34 hours or less, 33 hours or less, 32 hours or less, 31 hours or less, 30 hours or less, 29 hours or less, 28 hours or less, 27 hours or less, 26 hours or less, 25 hours or less, 24 hours or less, 23 hours or less, 22 hours or less, 21 hours or less, 20 hours or less, 19 hours or less, 18 hours or less, 17 hours or less, 16 hours or less, 15 hours or less, 14 hours or less, 13 hours or less, 12 hours or less, 11 hours or less, 10 hours or less, 9 hours or less, 8 hours or less, 7 hours or less, 6 hours or less, 5 hours or less, or 4 hours or less.
[0047] In the method for producing a magnetic material for hyperthermia containing iron nitride provided by the present invention, the time for heating the raw material of iron nitride is, for example, 3 hours or more, 4 hours or more, 5 hours or more, 6 hours or more, 7 hours or more, 8 hours or more, 9 hours or more, 10 hours or more, 11 hours or more, 12 hours or more, 13 hours or more, 14 hours or more, 15 hours or more, 16 hours or more, 17 hours or more, 18 hours or more, 19 hours or more, 20 hours or more, 21 hours or more, 22 hours or more, 23 hours or more, 24 hours or more, 25 hours or more, 26 hours or more, 27 hours or more, 28 hours or more, hours or more, 29 hours or more, 30 hours or more, 31 hours or more, 32 hours or more, 33 hours or more, 34 hours or more, 35 hours or more, 36 hours or more, 37 hours or more, 38 hours or more, 39 hours or more, 40 hours or more, 41 hours or more, 42 hours or more, 43 hours or more, 44 hours or more, 45 hours or more, 46 hours or more, 47 hours or more, 48 hours or more, 49 hours or more, 50 hours or more, 51 hours or more, 52 hours or more, 53 hours or more, 54 hours or more, 55 hours or more, 56 hours or more, 57 hours or more, 58 hours or more, 59 hours or more, 60 hours or more, 61 hours or more, 62 hours or more, 63 hours or more, 64 hours or more, 65 hours or more, 66 hours or more, 67 hours or more, 68 hours or more, 69 hours or more, 70 hours or more, 71 hours or more, 72 hours or more, 73 hours or more, 74 hours or more, 75 hours or more , 76 hours or more, 77 hours or more, 78 hours or more, 79 hours or more, 80 hours or more, 81 hours or more, 82 hours or more, 83 hours or more, 84 hours or more, 85 hours or more, 86 hours or more, 87 hours or more, 88 hours or more, 89 hours or more, 90 hours or more, 91 hours or more or more than 92 hours, 93 hours, 94 hours, 95 hours, 96 hours, 97 hours, 98 hours, 99 hours, 100 hours, 101 hours, 102 hours, 103 hours, 104 hours, 105 hours, 106 hours, 107 hours, 108 hours, 109 hours, 110 hours, 111 hours, 112 hours, 113 hours, 114 hours, 115 hours, 116 hours, 117 hours, 118 hours, or 119 hours.
[0048] In the method for producing a magnetic material for hyperthermia containing iron nitride provided by the present invention, the time for heating the raw material of iron nitride is within a range specified by, for example, any of the above upper limits and any of the above lower limits.
[0049] In the method for producing a magnetic material for hyperthermia containing iron nitride provided by the present invention, the raw material for iron nitride includes hematite, sodium amide, magnetite, ammonia gas, etc. Magnetite may be reduced to pure iron (α-Fe) by heat treatment in a hydrogen gas atmosphere.
[0050] By using the magnetic material for hyperthermia containing the iron nitride provided by the present invention, hyperthermia can be performed. That is, the present invention provides a method for hyperthermia, characterized by using the magnetic material for hyperthermia. In performing hyperthermia, the magnetic material for hyperthermia is administered to an affected part of a subject, and then the affected part of the subject to which the magnetic material for hyperthermia has been administered is placed under an alternating magnetic field to generate heat, and the cells in the affected part can be damaged by the generated heat. The subject is not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include mammals such as humans, mice, rats, cows, pigs, monkeys, dogs, and cats, but preferably humans. The affected part of the subject includes a site containing cancer cells. That is, the hyperthermia treatment method provided by the present invention can be a method for treating cancer.
[0051] The present invention provides a magnetic material for hyperthermia treatment, comprising the iron nitride, for use in a hyperthermia treatment method. The present invention also provides use of the iron nitride in the manufacture of a magnetic material for hyperthermia treatment, for use in a hyperthermia treatment method. EXAMPLES
[0052] Example 1: Testing Method: Hematite (Fe2O3) and sodium amide (NaNH2) were used as raw materials. They were weighed and sealed in a high-pressure reaction and decomposition vessel in a glove box with a N2 atmosphere (O2 concentration < 1.0%). This vessel was heated in an incubator at 230-260°C for 3-96 hours. After synthesis, the nanoparticles were washed with ethanol and dried overnight. The morphology, crystal structure, and nitrogen content of the synthesized nanoparticles were examined using a scanning electron microscope (SEM), an X-ray diffraction apparatus (XRD), and a CHN elemental analyzer, respectively, and the magnetic properties of the nanoparticles were evaluated using a vibrating sample magnetometer (VSM). In addition, the heat generation behavior of each particle was measured for 600 seconds under an AC magnetic field of 100 kHz and 125 Oe.
[0053] Results and Discussion: From the results of SEM observation and XRD measurement, the crystal phase of the samples synthesized under various conditions was ε-Fe 2-3 The nanoparticles synthesized at 250°C for 12 hours showed a temperature rise of about 20°C and exhibited the best heat generation characteristics under an alternating magnetic field (Fig. 1). Furthermore, the heat generation characteristics of the nanoparticles were significantly better than those of Fe3O4 nanoparticles. The VSM measurement results showed that the saturation magnetization and coercivity of the nanoparticles were 29.4 emu / g and 8 Oe, respectively. This example shows that ε-Fe is useful as a thermal species. 2-3 The synthesis conditions for ε-Fe N nanoparticles were found. 2-3 Since N nanoparticles showed higher heat generation properties than Fe3O4 nanoparticles, they are expected to be used as thermal sources. The methods for each experiment will now be described in more detail.
[0054] Example 2 Sample preparation method: In a glove box with a nitrogen atmosphere (oxygen concentration < 1.0%), 0.8 g of hematite (Fe2O3, manufactured by Nippon Kojundo Chemical Co., Ltd.) and 1.0 g of sodium amide (NaNH2, manufactured by Sigma-Aldrich Co., Ltd.) were mixed and placed in a carbon fiber-containing Teflon (registered trademark) crucible (HUTc-25 manufactured by San-ai Scientific Co., Ltd.) and sealed in a stainless steel outer cylinder (HUS-25 manufactured by San-ai Scientific Co., Ltd.). This container was heated in a constant temperature incubator (DKN-302, manufactured by Yamato Scientific Co., Ltd.) at 230 to 260 °C for 3 to 96 hours. After that, the sample was taken out, washed with ethanol, and dried overnight.
[0055] Example 3 EDS mapping: Testing Method: Carbon tape was attached to the sample stage, and a small amount of powder sample was placed on top of it. Excess sample was removed with an air duster. The sample was set according to the procedure of the machine (JEOL Field Emission Scanning Electron Microscope JSM-7900F (with EDS)) and measured at an accelerating voltage of 15 kV.
[0056] Results and Discussion: The results are shown in Figure 4. As shown in Figure 4, it was confirmed that nitrogen was filling the iron from the change in color of the mapping diagram. In addition, the numbers in the bottom right of the diagram represent the atomic percentages of iron, oxygen, and nitrogen in the entire mapping diagram, and it was confirmed that the amount of nitrogen filling the iron decreased over the course of reaction time.
[0057] Example 4 X-ray diffraction (XRD) measurements: Testing Method: An appropriate amount of the synthesized sample was taken and ground in a mortar and pestle. The ground powder sample was then placed in the recess of a glass sample plate. It was then flattened with another glass sample plate to make it the same height as the glass sample plate. Measurements were performed using a Rigaku desktop X-ray diffraction device (MiniFlex600) under the conditions described in the instructions. Specifically, measurements and calculations were performed under the following conditions. X-ray source:CuKα Voltage: 40 kV, current: 15 mA, 2θ scan rate: 10° / min. Calculation of crystallite size (D [nm]) (Scherrer formula)
number
[0058] Results and Discussion: The results are shown in Figures 2 and 3. As shown in Figures 2 and 3, the XRD data for this synthesis indicate that iron nitride with a hexagonal crystal system (hereafter referred to as ε-Fe 2-3 N). When the reaction time was changed from 6 to 96 hours, the peak shifted from the low angle side to the high angle side, and it was found that the peak changed from Fe2N to Fe3N. Based on the above results and the EDS results, it is considered that the nitrogen is removed by increasing the reaction time and it changes to Fe3N. And, by changing the reaction temperature from 230 to 260 °C, the peak intensity increased with the increase in reaction temperature. In addition, the integral width of the XRD peak decreased with the increase in reaction temperature, and when the integral width was calculated using the Scherrer formula, the crystallite size increased with the increase in reaction temperature. It is considered that the increase in reaction temperature promotes crystal growth.
[0059] Example 5 Heat generation characteristics: 80 mg of the sample was dispersed in 1.0 mL of agar phantom (agar concentration 1.1 wt%) in a 3.5 mL screw tube, and the temperature change of the agar phantom was measured using an optical fiber thermometer while an AC magnetic field was applied (for 10 minutes). The equipment and conditions used are as follows: AC magnetic field conditions: 100 kHz, 125 Oe AC magnetic field device: Toyo Electronics Co., Ltd. (custom-made product) Fiber optic thermometer: OpSens TMS-G4-10-100ST The positions of the three peaks used to estimate the crystallite size are shown below, along with the Miller indices (hlk).
[0060] Fe3N 2θ = 41.20° (0, 0, 2) 2θ = 43.69° (1, 1, 1) 2θ = 57.50° (1, 1, 2)
[0061] Fe2N 2θ = 40.83° (0,0,2) 2θ = 42.90° (-1, -1, 1) 2θ = 56.63° (-1, -1, 2)
[0062] The results are shown in Figures 1 and 5. As mentioned above, as shown in Figure 1, the nanoparticles synthesized under the conditions of 250°C and 12 hours showed a temperature rise of about 20°C, and exhibited the best heat generation characteristics under an AC magnetic field. In addition, as shown in Figure 5, it was revealed that the amount of heat generation changed depending on the change in the nitrogen content. Fe 2-3 It was found that the temperature rise behavior changed at the boundary of N_240d_12h.
Claims
1. A magnetic material for hyperthermia treatment comprising iron nitride, wherein the number of nitrogen atoms in the iron nitride measured by EDS mapping is 35% to 5% of the total number of atoms in the iron nitride.
2. 2. The magnetic material for hyperthermia treatment according to claim 1, wherein the number of nitrogen atoms in said iron nitride is 27% to 7% of the total number of atoms in said iron nitride.
3. 2. The magnetic material for hyperthermia treatment according to claim 1, wherein the number of nitrogen atoms in said iron nitride is 25% to 9% of the total number of atoms in said iron nitride.
4. 2. The magnetic material for hyperthermia treatment according to claim 1, wherein the number of nitrogen atoms in said iron nitride is 24% to 10% of the total number of atoms in said iron nitride.
5. 2. The magnetic material for hyperthermia treatment according to claim 1, wherein the number of iron atoms in said iron nitride is 20% to 80% of the total number of atoms in said iron nitride.
6. 2. The magnetic material for hyperthermia treatment according to claim 1, wherein the number of iron atoms in said iron nitride is 30% to 75% of the total number of atoms in said iron nitride.
7. 2. The magnetic material for hyperthermia treatment according to claim 1, wherein the number of iron atoms in said iron nitride is 40% to 70% of the total number of atoms in said iron nitride.
8. 2. The magnetic material for hyperthermia treatment according to claim 1, wherein the number of iron atoms in said iron nitride is 50% to 65% of the total number of atoms in said iron nitride.
9. A magnetic material for hyperthermia treatment comprising iron nitride, wherein a 2θ peak is measured at 42° to 44° by X-ray diffraction measurement of the iron nitride.
10. 10. The magnetic material for hyperthermia treatment according to claim 9, wherein a 2θ peak is measured at 42.5° to 44.0° by X-ray diffraction measurement of the iron nitride.
11. 10. The magnetic material for hyperthermia treatment according to claim 9, wherein a 2θ peak is measured at 43.0° to 43.7° by X-ray diffraction measurement of the iron nitride.
12. 10. The magnetic material for hyperthermia treatment according to claim 9, wherein a 2θ peak is measured at 43.2° to 43.7° by X-ray diffraction measurement of the iron nitride.
13. A method for producing a magnetic material for hyperthermia treatment containing iron nitride, comprising heating a raw material for iron nitride at 230-270°C for 3-120 hours.
14. 14. The method of claim 13, comprising heating the iron nitride source for between 6 hours and 50 hours.
15. 14. The method of claim 13, comprising heating the iron nitride source for 9 hours to 20 hours.
16. 14. The method of claim 13, comprising heating the iron nitride source at 235-265°C.
17. 14. The method of claim 13, comprising heating the iron nitride source at 245-255°C.
18. 14. The method of claim 13, wherein the source of iron nitride comprises hematite and sodium amide.
19. A method for hyperthermia treatment, comprising using the magnetic material for hyperthermia treatment according to any one of claims 1 to 12.
20. 20. The thermotherapy method according to claim 19, which is a method for treating cancer.
Citation Information
Patent Citations
Heating element for thermotherapy and manufacturing method therefor
JP2004105722A
Photolytic conversion process to form patterned amorphous films
JP2005505691A
Method for manufacturing ferromagnetic iron nitride grain powder, anisotropic magnet, bond magnet and powder-compact magnet
JP2013069926A
Method for manufacturing ferromagnetic iron nitride particle powder, anisotropic magnet, bonded magnet, and compressed-powder magnet
JP2013080922A